Solve for y -6-3=3-6y

Math
-6-3=3-6y
Rewrite the equation as 3-6y=-6-3.
3-6y=-6-3
Subtract 3 from -6.
3-6y=-9
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
-6y=-9-3
Subtract 3 from -9.
-6y=-12
-6y=-12
Divide each term by -6 and simplify.
Tap for more steps…
Divide each term in -6y=-12 by -6.
-6y-6=-12-6
Cancel the common factor of -6.
Tap for more steps…
Cancel the common factor.
-6y-6=-12-6
Divide y by 1.
y=-12-6
y=-12-6
Divide -12 by -6.
y=2
y=2
Solve for y -6-3=3-6y

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top